2022
DOI: 10.32725/det.2022.009
|View full text |Cite
|
Sign up to set email alerts
|

The migration of health care professionals from Hungary - global flows and local responses

Abstract: The migration of health care workers is a longstanding process which causes shortages in the sending countries. The Eastern enlargements of the European Union strengthened the East-West migration flows causing serious political controversies and jeopardising medical services. Hungary is also heavily affected by these processes and in the last 10 years; thousands of doctors and nurses left the country. Managing migration processes requires complex policy answers with the involvement of actors from various spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…First, we examine the migration of health professionals from a CEE perspective. Although there have already been several studies on the migration of health workers in CEE (e.g., [25][26][27]29,68]), the region shows several peculiarities. During the era of state socialism, there was essentially no shortage of health professionals in these countries, as the health systems here could develop in isolation from international processes and market mechanisms due to state paternalism.…”
Section: Introductionmentioning
confidence: 99%
“…First, we examine the migration of health professionals from a CEE perspective. Although there have already been several studies on the migration of health workers in CEE (e.g., [25][26][27]29,68]), the region shows several peculiarities. During the era of state socialism, there was essentially no shortage of health professionals in these countries, as the health systems here could develop in isolation from international processes and market mechanisms due to state paternalism.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of recent years has shown that this means mobility for employment and postgraduate training, starting from the residency period in more economically developed countries, with financial potential and/or adequate funding sources. From the perspective of the last two decades, we can appreciate that we are facing an exodus of specialists from healthcare units [ 16 , 17 ] with shortages of equipment and funding (from less developed countries), with already chronic imbalances in the employment of the medical sector [ 18 ], to medical units that offer the prospect of the future in excellence in health services, i.e., the smart association of technological transfer progress [ 19 ] with financial comfort through employment (so-called “decent employment”). Additionally, modern medicine has come to build a necessary balance between prevention and intervention as a form of efficiency for the quality of healthy life.…”
Section: Introductionmentioning
confidence: 99%
“…Students with a low level of income face difficulties in the migration process for studies. Most of the time, the expenses recorded in the countries of destination far exceed the level of those at home, and these expenses have a determining role in the migration decision [ 18 ]. For this reason, previously conducted studies [ 58 , 59 ] demonstrate the fact that wealthy students are more likely to migrate in order to continue their studies.…”
Section: Introductionmentioning
confidence: 99%